LINGUOCULTUROLOGY AS AN EMERGING FIELD IN CONTEMPORARY LINGUISTICS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the features of a new direction in linguistics—linguoculturology as an interdisciplinary and independent scientific discipline. Special attention is paid to its role in modern linguistics. The development and characteristics of Russian and European linguoculturological schools are examined.